Daylong Effect of Rinsing with Water Diluted Antiplaque®Toothpaste Combined with Toothbrushing on Volatile Sulphur Compound Levels - Anandina Irmagita; Gus Permana Subita; Siti Aliyah Pradono; Abdul Muthalib (Faculty of Dentistry, Universitas Indonesia, 2013)
Halitosis, complained by most adult population, is a common oral condition. About 8%% of the cases happened because of the microbia activity in the oral cavity that produces Volatile Sulphur Compound (VSC) which has unpleasant odour. Daily oral prophylaxis can reduce the oral VSC levels. Objective: to determine the daylong effect of Antiplque® toothpaste in daily oral prophylaxis: as dentrifice for tooth brushing and, in modified way, as oral rinse; on the VSC level. Methods: a double blind, clinical experimental study, involving 120 subjects with or without halitosis complain, divided in 2 treatment groups (oral rinse group and the combination of tooth brushing and oral rinse group, using Antiplaque® toothpaste) and 2 control groups (same procedure using placebo toothpaste). The daylong VSC levels measure with halimeter were taken twice, in the afternoon day I and day II. Results: there are significant reduction of daylong VSC levels (Wilcoxon signed rank test P<0.0%), but not in the treatment groups using the placebo toothpaste. The result on conbination of tooth brushing and oral rinse using Antiplaque® toothpaste are significant compared to the oral rinse treatment using Antiplaque® toothpaste alone (Mann Whitney, P<0.05). Conclusion: tooth brushing with Antiplaque® toothpaste combined with oral rinse using the modified Antiplaque® toothpaste can significantly reduce daylong VSC levels. DOI: 10.14693/jdi.v16i2.94